Penerapan Model Pembelajaran Guided Discovery Terhadap Prestasi Belajar Siswa Pada Materi Kalor di Kelas VII RSBI SMPN 1 Sidoarjo - Haryono, Heny Ekawati (saintis, 2016)
This paper reports the results of the research in observing the effect of the Guided Discovery learning model application to student achievement on heating the material in class VII SMPN 1 Sidoarjo RSBI. The goal was to determine the effect of the application of Guided Discovery models on student achievement, both in terms of affective, psychomotor and cognitive. The research design used was True Experimental Design. Determination of the study sample was randomly with details of class VII-2, VII-4 and VII-5 as the experimental class, while the class VII-3 as the control class. From the analysis of the cognitive aspects of students using t-test two parties and a t-test of the parties stated that the achievement of students in the experimental class was better than the control class that implements teacher center, while observations aspects of the psychomotor and affective students during the learning process said the rise of each meeting. Relations between the realm of achievement were analyzed using regression analysis and correlation with the result that states that every aspect of these achievements were related. By this it could be concluded that the application of the Model Guided Discovery positive effect on student achievement in the subject matter physics RSBI heat in class VII SMPN 1 Sidoarjo.